International express intermediate : - Macfarlane, Mike (Oxford Univ. Press, 1998)
A two-level general English course designed specifically for working adults at pre-intermediate and intermediate level. The emphasis is on covering the English they will need for work, travel, and socializing, by the use of serious, high-interest materials which will appeal to busy professionals.